PENGARUH FORMULASI RUMEN DENGAN DOSIS YANG BERBEDA TERHADAP SINTASAN BENIH IKAN NILA (Oreochromis niloticus) - Murni Murni; Abdul Malik; Farida Farida (Universitas Muhammadiyah Makassar, 2016)
This study aims to determine the effect of the application of the formulation of tilapia Oreochromis Niloticus. While the usefulness of a public information materials for farmers tilapia Oreochromis Niloticus in determining the type of feed the good order growth and increasing production. Research carried out for 2 months starting from September to October 2015 held at the Fish Farming Center, District Bontorannu, Gowa, South Sulawesi Province. Test animals used are tilapia fish age 1 month with a size of 3-5 cm a total of 120 individuals. Doses tested different treatments namely A (10%), B (15%), C (30 20%) and D controls. Data were analyzed using analysis of variance (ANOVA) followed by Tukey's test further. Results of research conducted during the two months showed that the mixing of the rumen to feed tilapia fish was lowest for the treatment of B (15%), without the mix feed the rumen which is highest in the control treatment.